Contradictory supranormal function in hydronephrotic kidneys: Fact or artifact on pediatric MAG-3 renal scans? - KIYAN, GÜRSU; ALPAY, HARİKA (LIPPINCOTT WILLIAMS & WILKINS, 2005)
Objectives: Contradictory supranormal renal function (SRF) in unilateral hydronephrosis is a debatable subject resulting from the methodology of nuclear renography or the characteristics of the patient. In this study, we aimed to investigate the frequency and comparison of SRF with MAG-3 scans by 8 different technical analyses in pediatric hydronephrosis. Methods: We reviewed Tc-99m MAG-3 scans in 82 children with unilateral hydronephrosis (52 male, 30 female, mean age: 47.7 +/- 64.5 months). Of 82, 34 also had Tc-99m DMSA scans. Data were reprocessed with 4 different regions of background activity (subrenal, perirenal C-type, perirenal ring, and lateral) at 2 different time intervals (1-2 and 2-3 minute), and 8 different estimates of MAG-3 differential renal function (DRF) were obtained in 67 patients. SRF was defined as DRY greater than 55% in the hydronephrotic kidney. Results: The routine processing protocol showed only 3 renal units with SRF, and all were on the right side (3.6%). After reprocessing, a total of 10 dilated kidneys had SRF in I or more of DRF estimates (5.2% of all estimations). These cases were significantly younger (8.1 +/- 6.7 vs. 42.5 +/- 52.5, P < 0.05) and had a larger renal area ratio (1.25 +/- .24 vs. 1.07 +/- .2 1, P < 0.05). There was no SRF with DMSA. In comparison between MAG-3 and DMSA DRY in 20 children who underwent both tests within 3 months, the best correlation was obtained when C-type correction was used for both agents at 2 time intervals (r: .86 and .84 for early and late time intervals, P < 0.00001, respectively). Conclusions: SRF in unilateral hydronephrosis is, at least, in part, technical in origin in this particular pediatric patient population with tubular immaturity (ie, physiological high background activity) and asymmetric kidney size.
Keywords: hydronephrosis; renography; differential renal function; supranormal function; artifact; UNILATERAL HYDRONEPHROSIS; CONGENITAL HYDRONEPHROSIS; BACKGROUND SUBTRACTION; DIURETIC RENOGRAPHY; HYDROURETERONEPHROSIS; CHILDREN; SCINTIGRAPHY; CONSENSUS; STANDARD